JUSTIFICATION OF THE PRODUCTION OF FUNCTIONAL PURPOSE BAKERY PRODUCTS FOR RESTAURANT ENTERPRISES (Development Service Industry Management, 2024)
Eating fatty fried food and sweets is clearly not compatible with the concept of a healthy lifestyle. But it is extremely difficult for many people to completely give up their favorite sweet desserts or a cup of sweet tea or invigorating coffee. Therefore, sugar substitutes and sweeteners, both natural and artificial, have been in great demand recently. Unfortunately, not all sugar alternatives are equally healthy. The benefit of stevia is that it helps regulate blood sugar levels, improves the work of the digestive and circulatory systems, and strengthens immunity. There are practically no contraindications to the use of "honey grass". Very few people have an individual intolerance to stevia. A unique medicinal plant can become one of the components of a diet and a healthy lifestyle. Unlike many artificially synthesized sugar substitutes, stevia does not cause a feeling of hunger. Stevia products are low in calories. In addition, stevia normalizes metabolic processes, naturally cleanses the body of toxins and other harmful substances.Bakery products with reduced sugar content are products with a functional purpose and are in high demand among the population. The analysis of the biochemical composition of stevia plant material showed the possibility of its use for the production of flour and confectionery products with reduced sugar content for own production in restaurants.The purpose of the research: development of the recipe of the latest technologies of bakery products with reduced sugar content for own production in restaurants.The existing technologies for the production of functional bakery products are considered. Analysis of the biochemical composition of stevia plant material showed the possibility of its use for the production of flour and confectionery products with reduced sugar content.The article develops a recipe for bakery products with reduced sugar content.
Keywords: bakery products; sugar; stevia; recipe; own production